고관절치환술 중 발생한 우심방 내 이행성 혈전에 의한 급성 폐동맥색전증 - 임문순; Moon Sun Im; 김윤기; Yun Gi Kim; 최원석; Won Suk Choi; 김학령; Hack Lyoung Kim; 김상현; Sang Hyun Kim; 조주희; Joo Hee Zo; et al. (The Korean journal of medicine, 2013)
저자들은 수술 전 정맥혈전 예방을 하지 않은 고령의 대퇴골 경부 골절 환자에서 수술 중 발생한 심인성 쇼크로 발현된 우심방 혈전을 심초음파로 진단하였던 1예를 경험하였다. 우심방 혈전에 의한 폐색전증은 치명적이나 예방 가능한 질환으로 본 증례를 통하여 폐색전증 예방의 중요성을 강조하는 바이다. Venous thromboembolism is a relatively common condition in inhospital patients, but it may also manifest as a lethal disease. However, the diagnosis is not suspected clinically in the vast majority of cases. Most hospitalized patients are at risk of venous thromboembolism, but the risk can be reduced significantly by appropriate prophylaxis. We herein report a case of a huge right atrial thrombus that presented as sudden cardiogenic shock during bipolar endoprosthesis of the hip due to a femoral neck fracture. Although the patient was elderly and immobile for 3 days before hip surgery, she did not receive prophylaxis for venous thromboembolism. More attention should be paid to venous thromboembolism prophylaxis in high-risk patients. (Korean J Med 2013;85:83-86)